Workaholism and Technostress During the COVID-19 Emergency: The Crucial Role of the Leaders on Remote Working - Spagnoli, Paola; Molino, Monica; Molinaro, Danila; Giancaspro, Maria Luisa; Manuti, Amelia; Ghislieri, Chiara (Frontiers in Psychology, 2020)
Although remote working in itself could bear several positive outcomes both for the employees and for the organizations, in the case of the sudden and forced remote working applied during the Covid-19 crisis the literature reported also the occurrence of negative aspects, one of these is technostress. In this context of crisis, leadership might be crucial to sustainably managing and supporting employees, especially those employees with workaholic tendencies who themselves are more prone to develop negative work and health outcomes. However, while research on the role of positive aspects of leadership during crises exists, the negative aspects of leadership during the Covid-19 crisis have not been studied yet. In view of the above, the present study aimed at providing a contribution on the role of authoritarian leadership in a sample of 339 University administrative employees - who worked completely from home or alternatively from home and from the workplace - by examining its moderating effect in the relationship between workaholism and technostress through conditional process analysis. Results pointed out that high authoritarian leadership had an enhancing effect whereas low authoritarian leadership had a protective effect on the relationship between workaholism and technostress, only in the group of complete remote workers. Thus, authoritarian leadership should be avoided and training leaders to be aware about its effect appears to be essential. Limitations, future directions for the study and practical implications are also discussed.